2000
DOI: 10.1046/j.1460-9592.2000.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of behavioural and physiological parameters for the assessment of postoperative analgesic demand in newborns, infants and young children: a comprehensive report on seven consecutive studies

Abstract: Summary Many different systems for the assessment of pain in newborns and infants have been tested for validity, rarely for reliability but never for sensitivity or specificity. We aimed to determine whether the assessment of an analgesic demand in the lower age group during the postoperative period is possible by observational methods only. In an repetitive and sequential prospective process for identifying observationable behaviour and measurable physiological parameters as indicators of a postoperative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
2
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(209 citation statements)
references
References 37 publications
6
183
2
18
Order By: Relevance
“…If there were no contraindications with the first dose given at the end of surgery, the following non-steroidal anti-inflammatory drugs were administered as part of multimodal analgesia management: niflumic acid 40 mg Á kg -1 rectally or ketoprofene 2 mg Á kg -1 iv twice daily and paracetamol 15 mg Á kg -1 iv or po four times daily. Pain scores for children \7 years old were evaluated by the Children and Infants Postoperative Pain Score (CHIPPS), 9 and pain scores in older children were evaluated by the visual analog scale (VAS) ranging from 0 = no pain to 10 = worst imaginable pain. If pain control was considered insufficient (i.e., VAS or CHIPPS score [3), nalbuphine 0.2 mg Á kg -1 (four times daily), tramadol 0.5 mg Á kg -1 (four times daily), or intravenous patientcontrolled morphine analgesia were administered as rescue analgesics.…”
Section: Methodsmentioning
confidence: 99%
“…If there were no contraindications with the first dose given at the end of surgery, the following non-steroidal anti-inflammatory drugs were administered as part of multimodal analgesia management: niflumic acid 40 mg Á kg -1 rectally or ketoprofene 2 mg Á kg -1 iv twice daily and paracetamol 15 mg Á kg -1 iv or po four times daily. Pain scores for children \7 years old were evaluated by the Children and Infants Postoperative Pain Score (CHIPPS), 9 and pain scores in older children were evaluated by the visual analog scale (VAS) ranging from 0 = no pain to 10 = worst imaginable pain. If pain control was considered insufficient (i.e., VAS or CHIPPS score [3), nalbuphine 0.2 mg Á kg -1 (four times daily), tramadol 0.5 mg Á kg -1 (four times daily), or intravenous patientcontrolled morphine analgesia were administered as rescue analgesics.…”
Section: Methodsmentioning
confidence: 99%
“…One must consider the lack of validated pain-assessment tools to evaluate ongoing pain and discomfort in mechanically ventilated preterm neonates. 54,75,76,88,116,123,124 Numerous randomized, controlled trials have evaluated pain control in mechanically ventilated newborns, but many have been underpowered. 19,39,102,[125][126][127][128] Two recent appropriately powered studies enrolled a total of 1048 neonates and demonstrated no differences in the incidence of severe intraventricular hemorrhage, periventricular leukomalacia, or death outcomes between the ventilated infants who received morphine or placebo infusions.…”
Section: Procedural Painmentioning
confidence: 99%
“…Therefore, many of the standard study instruments used for measuring the efficacy of analgesia or defining the goals of sedation or analgesia cannot be applied in this population. 123 The neonatal pain-control group discussed the difficulties of using pain-assessment scales. Many studies on methods for evaluating pain or distress in neonates have examined behaviors, physiologic parameters, and other variables as responses to pain.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of some other tools are: CHIPPS (which considers crying, facial expression, posture of trunk, posture of legs and motor restlessness) 2 , CRIES (which is an acronym for Crying, Requires oxygen to maintain a saturation > 95%, Increased blood pressure and heart rate, Expression, Sleep state) 3 and The Comfort Scale (in which variables are: alertness, calmness/agitation, respiratory response, physical movement, mean arterial pressure, heart rate, muscle tone and facial expression) 4 . Although these are simple and useful tools there is no correlation between pain scores and the treatment required, a limitation of these measurement methods.…”
mentioning
confidence: 99%